- Static Strength Analysis of a Top-Tensioned Riser in the Gendalo–Gehem Oil and Gas Field - I Gusti Ngurah Made Wirakusuma; Eva Yolanda; Nura Isyah; Naya Al Ramadhani; Muhammad Zubair Muis Alie (Departemen Teknik Kelautan Universitas Hasanuddin, 2026)
A Top-Tensioned Riser (TTR) is a key structural component that connects subsea facilities to floating production platforms and plays an essential role in ensuring production continuity in deepwater oil and gas exploitation systems. To maintain structural integrity, a TTR must satisfy the design requirements specified in API ST 2RD, particularly with respect to its ability to withstand hydrostatic pressure, internal fluid pressure, ocean current loads, and axial forces generated by top tension. This study aims to analyze the static strength of a TTR under deepwater conditions in the Gendalo–Gehem Field using a numerical approach based on the finite element method. The environmental loads considered include hydrostatic pressure at a water depth of 1,823 m, internal operating pressure, and hydrodynamic forces induced by ocean currents. The riser model was analyzed to determine stress distribution, deformation, and safety performance, which were then evaluated against the allowable stress limits defined in API ST 2RD. The analysis results indicate that the TTR exhibits a stable structural response, with the maximum stress remaining below the material yield strength. Although the maximum stress approaches the operational stress limit under conservative loading conditions, the riser still satisfies the ultimate limit state requirement. This study provides a preliminary basis for evaluating the feasibility of TTR design for deepwater operations in Indonesia and may serve as a reference for vertical riser design in floating production facilities.